A Comparative Risk-adjusted Performance Evaluation of South African SRI Funds and the FTSE/JSE over the Covid-19 Period - Sgammini, Ruschelle (International Journal of Economics and Financial Issues, 2023)
Socially responsible investing is a growing investment philosophy that has gained profound interest in both the local and international context. Socially conscious investors are seeking alternative ways to make more responsible investment choices, especially since the Covid-19 pandemic. Although financial markets experienced a significant decrease owing to the pandemic, a more positive outcome was eminent by an increased demand in SRI products during this period. The aim of this study was to evaluate the performance of local SRI funds before, during and after the Covid-19 period. Comparatively evaluating the performance relative to the FTSE/JSE Responsible Investment Index and All Share Index, will assist investors (those with a heightened desire to invest responsibly) to establish if SRI funds were able to provide higher risk-adjusted returns than the comparable SRI and general equity markets. The results indicated that although larger returns were produced by SRI funds during the Covid-19 period and that significant differences were found relative to the two indices, SRI funds were not able to consistently outperform either index. Thus, socially conscious investors are likely to achieve higher risk-adjusted returns from the SRI index, although not receiving diversification benefits from investing in funds.